Історія глобалізації: методологічні підходи та історіографія проблеми - Мартинов, А. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
У статті розглядаються історіографічні та методологічні проблеми досліджень історії глобалізації. Більша частина наукової продукції,
присвяченої зазначеній тематиці, з’являється наприкінці 1980-х років.
Відтоді сформувались основні історіографічні школи, які займаються
згаданим напрямком знань. Глобальні історичні дослідження, як аналітична модель, зосереджені на економічній історії, соціальній історії,
політичній історії, культурній історії, партійній історії, правовій історії, історії профспілок, історії технічного розвитку, історії громадських союзів, історії географічних відкриттів, локальній і регіональній історії,
ранній історії, історії античності, історії середньовіччя, історії нового
часу, історії сучасності. Modern theoreticians of Global History differ in opinion as to the
definition of Globalization and up till now there is no single definition, which
would satisfy most scientists. Some of them believe this phenomenon to be
irreal because it is impossible to clearly separate it from other social processes
and phenomena or because it do not has clearly defined place in the
geographical space. In most cases Globalization are understood as: We are
living today in an age of rapid globalization. Its pace has accelerated in the
past several decades, particularly since the end of the Cold War. The main
thrust for globalization involved a high degree of Westernization, it by no
means resulted in homogenization but everywhere produced diverse responses
to the West rooted in indigenous cultures. In fact, we have witnessed homogeneity
resulting from processes of globalization and at the some time
increasing heterogeneity. Globalization thus is extremely complex and variegated,
on the one hand indeed leading to high degrees of homogeneity in
economic organization, technological and scientific developments and even
lifestyles following Western patterns, on the other hand to marked divergences
from Western outlooks and practices and even to pronounced resistance to
Western influences. In this article we intend to examine the transformation of
historical thinking and writing within this larger global context.
Globalization is realized in the form of bilateral, multilateral and collective
relation. Global System is usually understood as hierarchically structurized
integral complex of actors of international relation, which are interconnected
by constant relations. Until the early 21th century the investigation of
Global History was performed within a whole number of social science:
philosophy, history, sociology, legal and economic sciences. The theory of
globalization is a science, which tries to logically and reasonably interpret the
most essential phenomena and processes as well as interrelation between them
using its own methods. Conflict and cooperation are the most important
manifestation of the state of international relations and logically proceed from
structural peculiarities of current global system.